Green-Synthesized Sm3+-Doped ZnO Nanoparticles for Multifunctional Applications - Lavanya R.; Ramakrishnappa T.; Girish K. M.; Suresh Kumar K.; Basavaraju N.; Shilpa B. M. (Advances in Materials Science and Engineering)
The present study focuses on the green-mediated synthesis of pristine and Sm3+-doped ZnO nanoparticles using Syzygium cumini fruit extract. The prepared material was characterized by various characterization techniques. Photocatalytic degradation of a fast orange red (FOR) dye under UV light resulted in 88% degradation, with a minimal decrease (87.90%) observed even after five successive runs, indicating the stability and effectiveness of the catalyst. The enhancement in degradation efficiency is attributed to the incorporation of Sm3+ ions into the ZnO lattice. Utilizing the optimized Sm3+ (5 mol%)-doped ZnO nanoparticles, cyclic voltammetry (CV) and electrochemical impedance spectra (EIS) were performed on the prepared electrode, demonstrating the excellent CV properties; this enhancement is attributed to the modification of ZnO’s redox chemistry and the alteration of charge transfer kinetics at the electrode-electrolyte interface due to the addition of Sm3+ into the ZnO structure. The antibacterial activity was performed against two pathogenic strains, i.e., Escherichia coli and Streptococcus aureus. The obtained results suggest that the prepared material holds great promise for catalytic, energy storage, antibacterial, and other multifunctional applications.